Strategi Manajemen Berbasis Tagline Dalam Memperkuat Kerja Sama International : Program Penguatan Citra Globab Universiti Malaysia Perlis ( UNIMAP). - Arifah, Rena; Alam, Hermansyah; Parinduri, Luthfi; Harahap, Raja; Hasibuan, Abdurrozaq (Jurnal Masyarakat Indonesia (Jumas), 2025)
In this era of globalization, international collaboration in higher education has become a key factor in improving academic quality, research, and technological development. Universiti Malaysia Perlis (UniMAP), as an institution that focuses on technical and vocational education, utilizes the philosophy encapsulated in its tagline: "Knowledge, Sincerity, Excellence" to strengthen its international position. This article aims to explore how UniMAP utilizes this tagline as a strategy to strengthen international collaboration and improve global performance. Through the implementation of strategies based on knowledge, sincerity, and excellence, UniMAP has not only improved the quality of education and research but also built sustainable international partnerships. Significant achievements are evident in its international rankings, collaborative research networks, and high graduate success rates. Despite challenges such as geographical limitations, cultural differences, and university competition, UniMAP has successfully overcome these obstacles by encouraging cross-cultural communication and building similar partnerships. The results of this study indicate that the values ​​embedded in UniMAP's tagline play a significant role in strengthening the university's international position and driving sustainable improvements in global performance. Keywords: UniMAP, International Collaboration, Tagline, Knowledge, Sincerity, Excellence, Technical Education, Global Performance